PERANCANGAN DAN IMPLEMENTASI WEBSITE PROFIL SEKOLAH DI SEKOLAH ADVENT MISSION SAGULUNG MENGGUNAKAN WORDPRESS DAN MYSQL - Muhamad Dody Firmansyah; Kelven LIong (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2022)
Mission Sagulung Adventist School is one of the schools that was established in 2007, the school still does not have a school profile website, school activities in conveying information are still through teachers who teach in class so there is a possibility of miscommunication between teachers and parents. The methodology used in this research is applied research that aims to solve the problems faced by Advent Mision Sagulung in digital era. The result of the research is school website called "Advent MIsion Sagulung".